Window module, vehicle, and thermoplastic elastomer composition manufacturing method
Patent Information
- Application Number
- JP2023127655
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2025-02-17
AI Technical Summary
【0019】 本発明に係る窓モジュールは、プライマー処理や接着剤塗布を行わなくても窓部と前記窓部の外周を覆う窓枠部とが強固に接着されるとともに、該窓枠部は摺動性及び復元性に優れたものとなる。
Smart Images

Figure 2025023497000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a window module, a vehicle equipped with the same, and a method for producing a thermoplastic elastomer composition. [Background technology]
[0002] A rubber sealant called a weatherstrip is used around the periphery of a vehicle window to prevent water, dust, sound, etc. from entering the vehicle interior. When connecting a vehicle window glass to a vehicle body panel via a weatherstrip, a polyurethane adhesive is generally used. Specifically, an adhesive is applied to the periphery of the window glass and the weatherstrip that holds up the window glass, and the adhesive is then attached to the vehicle body panel and pressed against it to connect the window glass. In order to improve adhesion with the polyurethane adhesive, a primer treatment is applied to the weatherstrip and the periphery of the window glass before the adhesive is applied (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2003-13006 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, after the primer treatment, the adhesive effect of the primer decreases over time, and the usable life is at most 10 days, and once this usable life has elapsed, the current situation is that the primer treatment must be carried out again.In addition, since the primer treatment and adhesive application are time-consuming, there is a demand for a technology that can firmly bond the vehicle window glass and weather strip without the primer treatment or adhesive application.
[0005] Some aspects of the present invention provide a window module in which a window portion and a window frame portion covering the outer periphery of the window portion are firmly bonded together, without the need for primer treatment or adhesive application. [Means for solving the problem]
[0006] The present invention has been made to solve at least a part of the above-mentioned problems, and can be realized in any of the following aspects.
[0007] One aspect of the window module according to the present invention is A window module having a window portion and a window frame portion covering an outer periphery of the window portion, The window frame portion is made of a composition containing the following component (T) and component (S): Component (T): A melt-kneaded product of a composition containing (A) at least one elastomer component selected from the group consisting of an olefin-based thermoplastic elastomer and a styrene-based thermoplastic elastomer, and (B) a thermoplastic resin (excluding those corresponding to component (S)). Component (S): a polymer having at least one functional group selected from the group consisting of a carboxy group, an acid anhydride group, an amino group, and a silanol group.
[0008] In one embodiment of the window module, The component (T) may be a melt-kneaded composition containing the component (A), the component (B), and a crosslinking agent (C).
[0009] In one embodiment of the window module, The polymer constituting the component (S) may be a propylene-based polymer.
[0010] In one embodiment of the window module, The polymer constituting the component (S) may be a styrene-based thermoplastic elastomer.
[0011] In one embodiment of the window module, The component (A) may contain an olefin-based thermoplastic elastomer (A1).
[0012] In one embodiment of the window module, The (A1) olefin-based thermoplastic elastomer may be an ethylene-propylene-non-conjugated diene copolymer.
[0013] In one embodiment of the window module, The component (A), (A2) may contain a block polymer having at least two polymer blocks selected from the group consisting of a polymer block A mainly composed of vinyl aromatic monomer units, a polymer block B mainly composed of conjugated diene monomer units, and a random polymer block C of vinyl aromatic monomer units and conjugated diene monomer units, or a hydrogenated product thereof.
[0014] In one embodiment of the window module, The component (B) may be an olefin resin.
[0015] In one embodiment of the window module, The window portion may have a wavelength in the range of 400 nm to 700 nm, at which the transmittance is 10% or more.
[0016] In one embodiment of the window module, The window portion may be made of glass, polycarbonate resin, or poly(meth)acrylate resin.
[0017] One aspect of the vehicle according to the present invention is The present invention is provided with a window module according to any one of the above aspects.
[0018] One embodiment of the method for producing a thermoplastic elastomer composition according to the present invention comprises the steps of: A first step of melt-kneading (A) at least one elastomer component selected from the group consisting of an olefin-based thermoplastic elastomer and a styrene-based thermoplastic elastomer, and (B) a thermoplastic resin (excluding those corresponding to component (S)); a second step of melt-kneading the melt-kneaded product obtained in the first step with a polymer having at least one functional group (S) selected from the group consisting of a carboxy group, an acid anhydride group, an amino group, and a silanol group; has. Effect of the Invention
[0019] The window module of the present invention has a window portion and a window frame portion covering the outer periphery of the window portion that are firmly bonded to each other without the need for primer treatment or adhesive application, and the window frame portion has excellent sliding properties and restoring properties. [Brief description of the drawings]
[0020] [Figure 1] FIG. 1 is a conceptual diagram illustrating an example of a window module according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] Preferred embodiments of the present invention will be described in detail below. Note that the present invention is not limited to the embodiments described below, and should be understood to include various modified examples that are implemented within the scope of the present invention.
[0022] In this specification, a numerical range described using "X to Y" is interpreted as including the numerical value X as the lower limit and including the numerical value Y as the upper limit.
[0023] In this specification, (A) at least one elastomer component selected from the group consisting of an olefin-based thermoplastic elastomer and a styrene-based thermoplastic elastomer is referred to as "component (A)", (A1) the olefin-based thermoplastic elastomer is referred to as "component (A1)", (A2) the styrene-based thermoplastic elastomer is referred to as "component (A2)", (B) the thermoplastic resin is referred to as "component (B)", (C) the crosslinking agent is referred to as "component (C)", (T) a melt-kneaded product of a composition containing components (A) and (B) is referred to as "component (T)", and (S) a polymer having at least one functional group selected from the group consisting of a carboxy group, an acid anhydride group, an amino group, and a silanol group is referred to as "component (S)".
[0024] 1. Window module Fig. 1 shows a window module 100 according to one embodiment of the present invention. As shown in Fig. 1, the window module 100 according to this embodiment has a window portion 10 and a window frame portion 12 that covers the outer periphery of the window portion 10. The window frame portion 12 is bonded to the peripheral portion of the window portion 10 in a state in which it holds up the peripheral portion of the window portion 10. The window frame portion 12 is composed of a composition containing the following component (T) and the following component (S). Component (T): A melt-kneaded product of a composition containing (A) at least one elastomer component selected from the group consisting of an olefin-based thermoplastic elastomer and a styrene-based thermoplastic elastomer, and (B) a thermoplastic resin (excluding those corresponding to component (S)). Component (S): a polymer having at least one functional group selected from the group consisting of a carboxy group, an acid anhydride group, an amino group, and a silanol group.
[0025] The window module 100 according to this embodiment is a window module that is used for a side door, a back door, a hood, a roof, etc. of a vehicle and includes a window portion 10 and a window frame portion 12. As shown in Fig. 1, the window module 100 according to this embodiment is modularized so that it can be immediately used in a body assembly process, etc., thereby improving the productivity of the vehicle.
[0026] The material constituting the window portion 10 can be selected from conventionally known materials as long as it is transparent. Here, "transparent" means that there is a wavelength within the range of 400 nm to 700 nm where the light transmittance of the plate-shaped molded product measured with a spectrophotometer is 10% or more.
[0027] Specific examples of materials constituting the window portion 10 include glass, polystyrene resin, high impact polystyrene resin, hydrogenated polystyrene resin, polyacrylstyrene resin, ABS resin, AS resin, AES resin, ASA resin, SMA resin, poly(meth)acrylate resin, polyphenyl ether resin, polycarbonate resin, amorphous polyalkylene terephthalate resin, polyester resin, amorphous polyamide resin, poly-4-methylpentene-1, cyclic polyolefin resin, amorphous polyarylate resin, polyethersulfone, thermoplastic elastomers such as styrene-based thermoplastic elastomers, olefin-based thermoplastic elastomers, polyamide-based thermoplastic elastomers, polyester-based thermoplastic elastomers, and polyurethane-based thermoplastic elastomers. Among these, glass is preferred from the viewpoints of impact resistance and heat resistance. Among these, polycarbonate resins and poly(meth)acrylate resins are preferred.
[0028] The components contained in the composition that constitutes the window frame portion 12 will be described below.
[0029] 1.1. Composition The composition that constitutes the window frame contains the above component (T) and component (S).
[0030] 1.1.1.(T) component Component (T) is a melt-kneaded composition containing (A) at least one elastomer component selected from the group consisting of olefin-based thermoplastic elastomers and styrene-based thermoplastic elastomers, and (B) a thermoplastic resin (excluding those corresponding to component (S)). Component (T) is also called dynamically crosslinked thermoplastic elastomer (TPV). Component (T) is a multiphase polymer material characterized by a sea-island structure in which component (A) is finely dispersed at a high density as a domain phase in component (B) which is a matrix phase.
[0031] The raw material components are melt-kneaded by a melt-kneading means using a general mixer such as a Banbury mixer, a single screw extruder, a twin screw extruder, a kneader, a multi-screw extruder, a roll, etc. Each component contained in the component (T) is described in detail below.
[0032] 1.1.1.1.(A) Component The composition constituting the window frame contains, as component (T), at least one elastomer component selected from the group consisting of (A1) an olefin-based thermoplastic elastomer and (A2) a styrene-based thermoplastic elastomer.
[0033] The content of component (A) in component (T) is preferably 10 to 80 parts by mass, more preferably 15 to 70 parts by mass, and particularly preferably 20 to 60 parts by mass, when the total mass of component (T) is taken as 100 parts by mass. When the content of component (A) in component (T) is within the above range, the injection moldability of the composition and the sliding properties and restoration of the window frame obtained by molding the composition are excellent.
[0034] <(A1) Olefin-based thermoplastic elastomer> The (A1) olefin-based thermoplastic elastomer is not particularly limited as long as it is a copolymer containing a repeating unit derived from an olefin, but is preferably an ethylene-α-olefin-non-conjugated diene copolymer, and more preferably an ethylene-propylene-non-conjugated diene copolymer. The (A1) component may be any of a random copolymer, an alternating copolymer, and a block copolymer, but is preferably a random copolymer.
[0035] The α-olefin is preferably an α-olefin having 3 to 10 carbon atoms, more preferably an α-olefin having 3 to 8 carbon atoms. Specific examples of the α-olefin include propylene, 1-butene, 2-methylpropene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, and 1-octene. Among these, propylene is particularly preferred. In synthesizing the component (A1), these α-olefins may be used alone or in combination of two or more.
[0036] Examples of the non-conjugated dienes include non-conjugated dienes having 5 to 15 carbon atoms, such as dicyclopentadiene, 5-ethylidene-2-norbornene, 1,4-hexadiene, 1,5-dicyclooctadiene, 7-methyl-1,6-octadiene, and 5-vinyl-2-norbornene. Among these, 5-ethylidene-2-norbornene and dicyclopentadiene are preferred.
[0037] The (A1) component may contain a repeating unit derived from a monomer other than ethylene, α-olefin, and non-conjugated diene. Examples of such monomers include conjugated dienes having 4 to 8 carbon atoms, such as 1,3-butadiene, 2-methyl-1,3-butadiene, 1,3-pentadiene, and 2,3-dimethyl-1,3-butadiene; vinyl carboxylates, such as vinyl acetate; unsaturated carboxylates, such as methyl acrylate, ethyl acrylate, butyl acrylate, methyl methacrylate, and ethyl methacrylate; and unsaturated carboxylic acids, such as acrylic acid and methacrylic acid. In synthesizing the (A1) component, these monomers may be used alone or in combination of two or more.
[0038] When the total mass of the component (A1) is taken as 100 mass%, the content of repeating units derived from ethylene in the component (A1) is preferably 40 to 85 mass%, more preferably 50 to 80 mass%, and particularly preferably 55 to 70 mass%.
[0039] When the total mass of the component (A1) is taken as 100 mass%, the content of repeating units derived from α-olefin in the component (A1) is preferably 10 to 50 mass%, more preferably 15 to 45 mass%, and particularly preferably 25 to 40 mass%.
[0040] When the total mass of the component (A1) is taken as 100 mass%, the content of repeating units derived from non-conjugated dienes in the component (A1) is preferably 1 to 15 mass%, more preferably 2 to 12 mass%, and particularly preferably 3 to 10 mass%.
[0041] When the total mass of the component (A1) is taken as 100 mass%, the content of repeating units derived from monomers other than ethylene, α-olefins, and non-conjugated dienes in the component (A1) is preferably 0 to 15 mass%, more preferably 0 to 8 mass%, and particularly preferably 0 to 5 mass%.
[0042] The content of the repeating units derived from each monomer in the (A1) component can be determined by infrared spectroscopy. Specifically, the infrared absorption spectrum of the (A1) component can be measured using an infrared spectrophotometer, and the content of the repeating units derived from each monomer in the (A1) component can be calculated according to the method described in "Characterization of Polyethylene by Infrared Absorption Spectroscopy (Takayama, Usami, et al.)" or "Die Makromolekulare Chemie, 177, 461 (1976) (McRae, MA, Madam S, WF, et al.)".
[0043] Specific examples of the (A1) component include ethylene-propylene copolymer, ethylene-1-butene copolymer, ethylene-1-hexene copolymer, ethylene-1-octene copolymer, ethylene-propylene-1-butene copolymer, ethylene-propylene-1-hexene copolymer, ethylene-propylene-1-octene copolymer, ethylene-propylene-5-ethylidene-2-norbornene copolymer, ethylene-propylene-dicyclopentadiene copolymer, ethylene-propylene-1,4-hexadiene copolymer, and ethylene-propylene-5-vinyl-2-norbornene copolymer. Among these, ethylene-propylene copolymer and ethylene-propylene-5-ethylidene-2-norbornene copolymer are preferred. These (A1) components may be used alone or in combination of two or more.
[0044] An example of the production method of component (A1) is a method of copolymerizing ethylene, an α-olefin, a non-conjugated diene, and other monomers in the presence of a known complex catalyst such as a Ziegler-Natta catalyst, a metallocene complex, a non-metallocene complex, etc. Examples of the polymerization method include a slurry polymerization method, a solution polymerization method, a bulk polymerization method, and a gas phase polymerization method.
[0045] The number average molecular weight of component (A1) is not particularly limited, but is preferably 100,000 or more, more preferably 150,000 or more, and even more preferably 170,000 or more, as a polystyrene-equivalent value measured by gel permeation chromatography. The number average molecular weight of component (A1) is not particularly limited, but is preferably 600,000 or less, more preferably 550,000 or less, and particularly preferably 500,000 or less, as a polystyrene-equivalent value measured by gel permeation chromatography.
[0046] <(A2) Styrene-based thermoplastic elastomer> The (A2) styrene-based thermoplastic elastomer is preferably a block polymer having at least two polymer blocks selected from the group consisting of a polymer block A mainly composed of vinyl aromatic monomer units, a polymer block B mainly composed of conjugated diene monomer units, and a random polymer block C of vinyl aromatic monomer units and conjugated diene monomer units, or a hydrogenated product thereof.
[0047] Here, the term "mainly composed of" means that the target monomer unit is contained in the target polymer block in an amount of 50 mol % or more.
[0048] The vinyl aromatic monomer is not particularly limited, and examples thereof include styrene, α-methylstyrene, p-methylstyrene, divinylbenzene, 1,1-diphenylethylene, N,N-dimethyl-p-aminoethylstyrene, N,N-diethyl-p-aminoethylstyrene, etc. Among these, styrene, α-methylstyrene, and p-methylstyrene are preferred, and styrene is more preferred.
[0049] The conjugated diene monomer is not particularly limited, and examples thereof include 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 2-methyl-1,3-pentadiene, 1,3-hexadiene, etc. Among these, 1,3-butadiene and 2-methyl-1,3-butadiene are preferred, and 1,3-butadiene is more preferred.
[0050] The polymer block A may be composed of one type of vinyl aromatic monomer unit, or may be composed of two or more types of vinyl aromatic monomer units. The polymer block A may contain a monomer unit other than the vinyl aromatic monomer unit.
[0051] The polymer block B may be composed of one kind of conjugated diene monomer unit, or may be composed of two or more kinds of conjugated diene monomer units. The polymer block B may contain a monomer unit other than the conjugated diene monomer unit.
[0052] The polymer block C may be composed of one type of vinyl aromatic monomer unit and one type of conjugated diene monomer unit, two or more types of vinyl aromatic monomer units and one type of conjugated diene monomer unit, one type of vinyl aromatic monomer unit and two or more types of conjugated diene monomer unit, or two or more types of vinyl aromatic monomer units and two or more types of conjugated diene monomer units. The polymer block C may contain monomer units other than the vinyl aromatic monomer units and the conjugated diene monomer units.
[0053] In the block copolymer of component (A2), the mass proportion of block A mainly composed of vinyl aromatic monomer units is preferably 5 mass% or more, more preferably 10 mass% or more. In the block copolymer of component (A2), the mass proportion of block A mainly composed of vinyl aromatic monomer units is preferably 55 mass% or less, more preferably 50 mass% or less, and particularly preferably 45 mass% or less.
[0054] The chemical structure of the block copolymer of component (A2) may be any of linear, branched, radial, etc., but is preferably a block copolymer represented by the following formula (1) or (2), and from the viewpoint of improving mechanical strength, is more preferably a structure represented by the following formula (1).
[0055] A-(BA)m (1) (AB)n (2) In the formula, A represents polymer block A. B represents polymer block B. m represents an integer of 1 to 5. n represents an integer of 2 to 5. When a plurality of polymer blocks A and a plurality of polymer blocks B are present, the monomer units contained therein may be the same or different.
[0056] From the viewpoint of rubber elasticity of the composition, the component (A2) is preferably a block copolymer represented by the above formula (1), more preferably a block copolymer represented by formula (1) in which m is 3 or less, even more preferably a block copolymer represented by formula (1) in which m is 2 or less, and particularly preferably a block copolymer represented by formula (1) in which m is 1.
[0057] The component (A2) may be a hydrogenated product of a block copolymer having at least two polymer blocks selected from the group consisting of a polymer block A mainly composed of vinyl aromatic monomer units, a polymer block B mainly composed of conjugated diene monomer units, and a random polymer block C of vinyl aromatic monomer units and conjugated diene monomer units.
[0058] The hydrogenation method and reaction conditions of the block copolymer are not particularly limited, and are usually carried out at 20 to 150° C. under a hydrogen pressure of 0.1 to 10 MPa in the presence of a hydrogenation catalyst. In this case, the hydrogenation rate can be appropriately adjusted by changing the amount of the hydrogenation catalyst, the hydrogen pressure during the hydrogenation reaction, the reaction time, etc.
[0059] Examples of the hydrogenation catalyst include those described in JP-A-1-275605, JP-A-5-271326, JP-A-5-271325, JP-A-5-222115, JP-A-11-292924, JP-A-2000-37632, JP-A-59-133203, JP-A-63-5401, JP-A-62-218403, JP-A-7-90017, JP-B-43-19960, and JP-B-47-40473. The hydrogenation catalysts may be used alone or in combination of two or more.
[0060] Specific examples of the (A2) component include styrene-butadiene-styrene block copolymers, styrene-isoprene-butadiene-styrene block copolymers, and hydrogenated versions of these. An example of a hydrogenated version of a styrene-butadiene-styrene block copolymer is styrene-ethylene-butylene-styrene copolymer (SEBS). An example of a hydrogenated version of a styrene-isoprene-butadiene-styrene block copolymer is styrene-ethylene-ethylene-propylene-styrene copolymer (SEEPS). Among these, the hydrogenated version of a styrene-butadiene-styrene block copolymer is preferred because it tends to have high fluidity and good fusion properties.
[0061] The number average molecular weight of component (A2) is not particularly limited, but is preferably 100,000 or more, more preferably 150,000 or more, and even more preferably 170,000 or more, as a polystyrene-equivalent value measured by gel permeation chromatography. The number average molecular weight of component (A2) is not particularly limited, but is preferably 600,000 or less, more preferably 550,000 or less, and particularly preferably 500,000 or less, as a polystyrene-equivalent value measured by gel permeation chromatography.
[0062] 1.1.1.2.(B) Component The composition constituting the window frame contains a thermoplastic resin (B) (excluding those corresponding to the component (S) described below) as the component (T). Examples of the component (B) include olefin-based resins; polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, and polylactic acid; acrylic resins; styrene-based resins such as polystyrene, AS resin, and ABS resin; polyamides such as nylon 6, nylon 6,6, nylon 12, semi-aromatic polyamides (nylon 6T, nylon 6I, and nylon 9T), and modified polyamides; polycarbonate, polyacetal, fluororesin, modified polyphenylene ether, polyphenylene sulfide, polyester elastomer, polyarylate, liquid crystal polymers (fully aromatic and semi-aromatic), polysulfone, polyethersulfone, polyetheretherketone, polyetherimide, polyamideimide, polyimide, and polyurethane-based resins. These components (B) may be used alone or in combination of two or more.
[0063] Among these (B) components, olefin resins are preferred from the viewpoint of good compatibility with (A) component. Examples of olefin resins include homopolymers of α-olefins having about 2 to 8 carbon atoms, such as ethylene, propylene, and 1-butene; binary or ternary copolymers of these α-olefins with other α-olefins having about 2 to 18 carbon atoms, such as ethylene, propylene, 1-butene, 3-methyl-1-butene, 1-pentene, 4-methyl-1-pentene, 4,4-dimethyl-1-pentene, 1-hexene, 4-methyl-1-hexene, 1-heptene, 1-octene, 1-decene, and 1-octadecene.
[0064] Specific examples of olefin-based resins include ethylene-based resins such as ethylene homopolymer, ethylene-propylene copolymer, ethylene-1-butene copolymer, ethylene-propylene-1-butene copolymer, ethylene-4-methyl-1-pentene copolymer, ethylene-1-hexene copolymer, ethylene-1-heptene copolymer, and ethylene-1-octene copolymer; propylene-based resins such as propylene homopolymer, propylene-ethylene copolymer, and propylene-ethylene-1-butene copolymer; 1-butene-based resins such as 1-butene homopolymer, 1-butene-ethylene copolymer, and 1-butene-propylene copolymer; and 4-methyl-1-pentene-based resins such as 4-methyl-1-pentene homopolymer and 4-methyl-1-pentene-ethylene copolymer.
[0065] These olefin-based resins may be used alone or in combination of two or more. Among these, ethylene-based resins and propylene-based resins are preferred, propylene-based resins are more preferred, and propylene homopolymers are particularly preferred.
[0066] The content of component (B) in component (T) is preferably 1 to 50 parts by mass, more preferably 5 to 40 parts by mass, and particularly preferably 10 to 30 parts by mass, when the total mass of component (T) is 100 parts by mass. When the content of component (B) in component (T) is within the above range, the injection moldability of the composition and the sliding properties and restoration of the window frame obtained by molding the composition are excellent.
[0067] 1.1.1.3.(C) Crosslinking Agent The composition constituting the window frame preferably contains a crosslinking agent (C) as component (T). Examples of component (C) include organic peroxides, phenolic crosslinking agents, sulfur, sulfur compounds, p-quinone, p-quinone dioxime derivatives, epoxy compounds, silane compounds, amino resins, etc. Among these, organic peroxides and phenolic crosslinking agents are preferred, and organic peroxides are more preferred.
[0068] <Organic peroxide> Examples of the organic peroxides include 1,3-di(tert-butylperoxyisopropyl)benzene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne-3, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexene-3, 1,3-bis(tert-butylperoxyisopropyl)benzene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,2-di(tert-butylperoxy)-p-isopropylbenzene, dicumyl peroxide, di-tert-butyl peroxide, tert-butyl peroxide, t Examples of organic peroxides include ert-butylcumyl peroxide, p-menthane peroxide, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, dilauroyl peroxide, diacetyl peroxide, tert-butyl peroxybenzoate, 2,4-dichlorobenzoyl peroxide, p-chlorobenzoyl peroxide, benzoyl peroxide, di(tert-butylperoxy)perbenzoate, n-butyl-4,4-bis(tert-butylperoxy)valerate, tert-butylperoxyisopropyl carbonate, etc. Among these organic peroxides, dialkyl peroxides such as 1,3-bis(tert-butylperoxyisopropyl)benzene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne-3, and 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane are preferred.
[0069] From the viewpoint of achieving uniform and gentle partial crosslinking, the content of the organic peroxide is preferably 0.01 to 2.0 parts by mass, and more preferably 0.02 to 1.5 parts by mass, per 100 parts by mass of the total of the (A) component, the (B) component, and the mineral oil-based softener.
[0070] (C) When an organic peroxide is used as a crosslinking agent, by using a polyfunctional compound having high reactivity with free radicals generated during melt kneading as a crosslinking auxiliary, the crosslinking reaction can proceed quickly to form rubber domains with high crosslink density, and side reactions other than the crosslinking reaction of free radicals (for example, disproportionation reaction between free radical species, hydrogen abstraction reaction not involved in the crosslinking reaction, and β-elimination reaction accompanied by main chain scission of copolymer rubber or polyolefin resin) can be suppressed.
[0071] Here, the term "polyfunctional compound" refers to a low molecular weight compound having two or more non-conjugated carbon-carbon double bonds in one molecule, which, when used in combination with another crosslinking agent that does not have the same double bonds, can efficiently promote the crosslinking reaction and produce a uniform crosslinked structure and excellent rubber elasticity.
[0072] Examples of the polyfunctional compound include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, diallyl phthalate, diallyl terephthalate, tetraallyloxyethane, triallyl cyanurate, N,N'-m-phenylene bismaleimide, N,N'-toluylene bismaleimide, bis(3-ethyl-5-methyl-4-maleimidophenyl)methane, divinylbenzene, zinc di(meth)acrylate, etc. These polyfunctional compounds may be used alone or in combination of two or more.
[0073] From the viewpoint of maintaining uniformity of the phase structure and moldability, the content of the polyfunctional compound is preferably 3 parts by mass or less, more preferably 0.1 to 1.5 parts by mass, and particularly preferably 0.2 to 1.2 parts by mass, per 100 parts by mass of the total of component (A), component (B), and mineral oil-based softener.
[0074] <Phenol-based crosslinking agent> Examples of the phenol-based crosslinking agent include p-substituted phenol-based compounds represented by the following general formula (3), o-substituted phenol-aldehyde condensates, m-substituted phenol-aldehyde condensates, and brominated alkylphenol-aldehyde condensates. In particular, p-substituted phenol-based compounds are preferred. [ka] (In formula (3), n is an integer of 0 to 10, X is at least one of a hydroxyl group, a halogenated alkyl group, and a halogen atom, and R is a saturated hydrocarbon group having 1 to 15 carbon atoms.)
[0075] The p-substituted phenol compound can be obtained by a condensation reaction between a p-substituted phenol and an aldehyde (preferably formaldehyde) in the presence of an alkali catalyst.
[0076] From the viewpoint of uniform and mild partial crosslinking, the content of the phenol-based crosslinking agent is preferably 0.1 to 10 parts by mass, more preferably 0.3 to 5 parts by mass, and particularly preferably 0.4 to 2 parts by mass, relative to 100 parts by mass of the total of the (A) component, the (B) component, and the mineral oil-based softener.
[0077] When using a phenol-based crosslinking agent, a crosslinking assistant may be used in combination. Examples of crosslinking assistants that can be used in combination with the phenol-based crosslinking agent include metal halides such as stannous chloride and ferric chloride; and organic halides such as chlorinated polypropylene, brominated polypropylene, brominated butyl rubber, and chloroprene rubber. In addition to the above crosslinking assistants, metal oxides such as zinc oxide and dispersants such as stearic acid may be used in combination.
[0078] Other ingredients The composition constituting the window frame may contain various additives as component (T) as necessary. Examples of such additives include mineral oil-based softeners, softeners other than mineral oil-based softeners, lubricants, antioxidants, heat stabilizers, weathering agents, metal deactivators, ultraviolet absorbers, light stabilizers, copper damage inhibitors and other stabilizers, antibacterial and antifungal agents, dispersants, plasticizers, crystal nucleating agents, flame retardants, silicone oils, silicone polymers, tackifiers, foaming assistants, colorants such as titanium oxide and carbon black, metal powders such as ferrite, inorganic fibers such as glass fibers and metal fibers, organic fibers such as carbon fibers and aramid fibers, composite fibers, inorganic whiskers such as potassium titanate whiskers, glass beads, glass balloons, glass flakes, asbestos, mica, calcium carbonate, talc, silica, calcium silicate, hydrotalcite, kaolin, diatomaceous earth, graphite, pumice, ebonized powder, cotton flock, cork powder, barium sulfate, fluororesins, polymer beads and other fillers or mixtures thereof, polyolefin wax, cellulose powder, rubber powder, wood powder and other fillers, low molecular weight polymers and the like.
[0079] <Mineral oil-based softener> The mineral oil-based softener preferably has a weight average molecular weight of 300 to 2000, particularly preferably 500 to 1500. The rubber softener made of mineral oil-based hydrocarbon is Generally, oils are classified as follows: paraffin oils are mixtures of aromatic rings, naphthenic rings, and paraffin chains, in which the number of carbon atoms in the paraffin chains accounts for 50% or more of the total number of carbon atoms; naphthenic oils are those in which the number of carbon atoms in the naphthenic rings accounts for 30-45% of the total number of carbon atoms; and aromatic oils are those in which the number of carbon atoms in the aromatic rings accounts for 30% or more of the total number of carbon atoms. In the present invention, paraffin oils are preferred, and hydrogenated paraffin oils are particularly preferred. Mineral oil-based hydrocarbons have a kinetic viscosity at 40°C of 2×10 -5 ~8×10 -4 m 2 / s (20~800cSt), especially 5×10 -5 ~6×10 -4 m 2 / s (50 to 600 cSt), and a pour point of -40 to 0°C, particularly -30 to 0°C, is preferred.
[0080] <Softeners other than mineral oils> The softener other than the mineral oil-based softener is not particularly limited as long as it is a commonly used rubber softener, and examples thereof include vegetable oils (coconut oil, etc.), esters of fatty acids and higher alcohols (phthalic acid diesters, etc.), phosphate triesters, polybutenes, polybutadienes, and other low molecular weight hydrocarbons.
[0081] <Anti-aging agent> By including an antioxidant in the composition constituting the window frame portion, thermal decomposition is suppressed and the composition can withstand molding at high temperatures, and the heat resistance of the fused portion between the window frame portion and the window portion obtained by molding the composition may be improved.
[0082] Examples of the antiaging agent include hindered amine compounds, hydroquinone compounds, hindered phenol compounds, sulfur-containing compounds, phosphorus-containing compounds, naphthylamine compounds, diphenylamine compounds, p-phenylenediamine compounds, quinoline compounds, hydroquinone derivative compounds, monophenol compounds, bisphenol compounds, trisphenol compounds, polyphenol compounds, thiobisphenol compounds, hindered phenol compounds, phosphite compounds, imidazole compounds, nickel dithiocarbamate compounds, phosphoric acid compounds, etc. These antiaging agents may be used alone or in combination of two or more.
[0083] As the antioxidant, commercially available products may be used, for example, products under the trade names "ADK STAB AO-60", "ADK STAB 2112", and "ADK STAB AO-412S" manufactured by ADEKA Corporation.
[0084] 1.1.2.(S) component The composition constituting the window frame contains, as component (S), a polymer having at least one functional group (hereinafter also referred to as a "specific functional group") selected from the group consisting of a carboxy group, an acid anhydride group, an amino group, and a silanol group. By containing, as component (S), a polymer having a specific functional group, the window and the window frame covering the outer periphery of the window can be firmly bonded together without the need for primer treatment or adhesive application.
[0085] Examples of the polymer having a specific functional group include, but are not limited to, an acid and / or its derivative-modified polyolefin polymer, an amino group-modified polyolefin polymer, a silanol group-modified polyolefin polymer, an acid and / or its derivative-modified styrene-based thermoplastic elastomer, an amino group-modified styrene-based thermoplastic elastomer, a silanol group-modified styrene-based thermoplastic elastomer, etc. The polymer having a specific functional group is obtained by modifying a polyolefin polymer or a styrene-based thermoplastic elastomer used as a raw material with a compound having a specific functional group (hereinafter also referred to as a "modifier").
[0086] As the polyolefin polymer that can be used as the raw material, it is preferable to use polypropylene polymers such as propylene homopolymers and propylene-ethylene copolymers. Among these, propylene homopolymer is more preferred from the viewpoint of obtaining higher adhesion between the window portion and the window frame portion. Furthermore, the polyolefin-based polymer may be either crystalline or amorphous.
[0087] Styrenic thermoplastic elastomers that can be used as raw materials include styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene-styrene block copolymer (SIS), styrene-ethylene-butylene-styrene block copolymer (SEBS), and styrene-ethylene-propylene-styrene block copolymer (SEPS).
[0088] The acid used for modification is preferably an unsaturated carboxylic acid. The unsaturated carboxylic acid is not particularly limited, but may be acrylic acid, methacrylic acid, crotonic acid, maleic acid, fumaric acid, cinnamic acid, itaconic acid, hymic acid, or citraconic acid. The derivatives of the unsaturated carboxylic acid may be anhydrides, esters, amides, imides, or metal salts of these acids.
[0089] Specific examples of the derivatives of unsaturated carboxylic acids include maleic anhydride, himic anhydride, itaconic anhydride, citraconic anhydride, methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, glycidyl acrylate, glycidyl methacrylate, maleic acid monoethyl ester, maleic acid diethyl ester, itaconic acid monomethyl ester, itaconic acid diethyl ester, acrylamide, methacrylamide, maleic acid monoamide, maleic acid diamide, maleic acid-N-monoethylamide, maleic acid-N,N-diethylamide, maleic acid-N-monobutylamide, maleic acid-N,N-dibutylamide, fumaric acid monoamide, fumaric acid diamide, fumaric acid-N-monobutylamide, fumaric acid-N,N-dibutylamide, maleimide, N-butylmaleimide, N-phenylmaleimide, sodium acrylate, sodium methacrylate, potassium acrylate, and potassium methacrylate.
[0090] These acids and / or derivatives thereof may be used alone or in combination of two or more.
[0091] Compounds having an amino group used for modification include N,N-dimethylvinylbenzylamine, N,N-diethylvinylbenzylamine, N,N-dipropylvinylbenzylamine, N,N-dibutylvinylbenzylamine, N,N-diphenylvinylbenzylamine, 2-dimethylaminoethylstyrene, 2-diethylaminoethylstyrene, 2-bis(trimethylsilyl)aminoethylstyrene, and 1-(4-N,N-dimethylaminophenyl)-1-phenylethylene. , N,N-dimethyl-2-(4-vinylbenzyloxy)ethylamine, 4-(2-pyrrolidinoethyl)styrene, 4-(2-piperidinoethyl)styrene, 4-(2-hexamethyleneiminoethyl)styrene, 4-(2-morpholinoethyl)styrene, 4-(2-thiazinoethyl)styrene, 4-(2-N-methylpiperazinoethyl)styrene, 1-((4-vinylphenoxy)methyl)pyrrolidine, 1-(4-vinylbenzyloxymethyl)pyrrolidine, etc. These compounds having an amino group may be used alone or in combination of two or more.
[0092] Examples of compounds having an alkoxysilyl group used for modification include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, 3-(N-phenyl)aminopropyltrimethoxysilane, 3-(N-phenyl)aminopropyltriethoxysilane, and vinyltriethoxysilane. A silanol group-modified polyolefin polymer or a silanol group-modified styrene thermoplastic elastomer can be obtained by modifying a polyolefin polymer or a styrene thermoplastic elastomer with a compound having an alkoxysilyl group, and then hydrolyzing the alkoxysilyl group. These compounds having an alkoxysilyl group may be used alone or in combination of two or more.
[0093] The amount of the modifier used to modify the polyolefin polymer or styrene-based thermoplastic elastomer is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, based on 100 parts by mass of the polyolefin polymer or styrene-based thermoplastic elastomer used as a raw material. On the other hand, the amount of the modifier used to modify the polyolefin polymer or styrene-based thermoplastic elastomer is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, based on 100 parts by mass of the polyolefin polymer or styrene-based thermoplastic elastomer used as a raw material. If the amount of the modifier used is the above lower limit or more, the adhesiveness of the obtained composition tends to be good, while if the amount is the above upper limit or less, the generation of unreacted substances and by-products is suppressed, and the deterioration of the product appearance and the decrease in adhesiveness tend to be suppressed in the window frame part composed of the obtained composition.
[0094] The modification with the above-mentioned modifier is preferably graft modification, and can be carried out by various conventionally known methods. The modification method includes, but is not limited to, a melt modification method in which a modifier is added to a molten polyolefin polymer or a styrene-based thermoplastic elastomer and graft copolymerized, a solution modification method in which a modifier is added to a polyolefin polymer or a styrene-based thermoplastic elastomer dissolved in a solvent and graft copolymerized, and a solid phase polymerization method in which a modifier is added to a solid polyolefin polymer or a styrene-based thermoplastic elastomer and graft copolymerized.
[0095] The number average molecular weight of the polymer having a specific functional group is not particularly limited, but is preferably 20,000 or more, and more preferably 20,000 or more and 300,000 or less.
[0096] The melt flow rate (MFR) of the polymer having a specific functional group is not particularly limited, but is preferably 0.01 to 3000 g / 10 min, more preferably 0.1 to 2500 g / 10 min, and particularly preferably 1 to 100 g / 10 min. Here, the MFR of the polymer having a specific functional group means a value measured according to JIS K7210:1999 under conditions of a measurement temperature of 230° C. and a measurement load of 21.2 N.
[0097] The content of component (S) in the composition constituting the window frame is preferably 1 to 30 parts by mass, more preferably 2 to 25 parts by mass, and particularly preferably 3 to 20 parts by mass, per 100 parts by mass of component (T). When the content of component (S) is within the above range, sufficient adhesive strength between the window portion and the window frame tends to be obtained.
[0098] 1.2. Method for producing the composition The production of a composition according to one embodiment of the present invention includes a first step of melt-kneading (A) at least one elastomer component selected from the group consisting of an olefin-based thermoplastic elastomer and a styrene-based thermoplastic elastomer, and (B) a thermoplastic resin (excluding those corresponding to the component (S)), and a second step of melt-kneading the melt-kneaded product obtained in the first step with (S) a polymer having at least one functional group selected from the group consisting of a carboxy group, an acid anhydride group, an amino group, and a silanol group.
[0099] In the present invention, the term "melt-kneading" refers to both applying a shear force and heating. In the first step, the component (A) and the component (B) are melt-kneaded to obtain a composition comprising: In the second step, the melt-kneaded product obtained in the first step is melt-kneaded with a polymer (S) having at least one functional group selected from the group consisting of a carboxy group, an acid anhydride group, an amino group, and a silanol group, to obtain a melt-kneaded product having an island-sea structure in which the components (A) and (S) are dispersed as dispersed phases (island phases) in the continuous phase (sea phase) of the component (B).
[0100] Examples of devices capable of melt kneading include an open-type mixing roll, a non-open-type Banbury mixer, a kneader, a single-screw extruder, a co-rotating continuous twin-screw extruder, a counter-rotating continuous twin-screw kneader, etc. The process carried out in this kneading device may be either a batch type or a continuous type.
[0101] From the viewpoint of the balance between the melting of the (A), (B), and (S) components and the crosslinking reaction, the melt-kneading temperature is preferably in the range of 150 to 250° C. The melt-kneading treatment time is not particularly limited, but is usually 0.1 to 30 minutes in consideration of productivity, etc.
[0102] 2. Working Example The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the examples and comparative examples, "%" or "parts" is based on mass unless otherwise specified.
[0103] 2.1. Production of thermoplastic elastomer composition The types and amounts of ethylene-α-olefin copolymer rubber, hydrogenated block copolymer, polyolefin resin, mineral oil-based softener, crosslinking agent, crosslinking assistant, antioxidant, and polydimethylsiloxane shown in Table 1 below were melt-kneaded to produce thermoplastic elastomer compositions (T-1) to (T-5). Next, any one of the thermoplastic elastomer compositions (T-1) to (T-5) of the type and amount shown in Table 2 below was melt-kneaded with the acid anhydride group-containing polyolefin (S-1) or the silanol group-containing polyolefin (S-2) to produce each of the thermoplastic elastomer compositions used in Examples 1 to 8. In Comparative Examples 1 to 5, the thermoplastic elastomer compositions (T-1) to (T-5) were used as they were.
[0104] 2.2. Evaluation method (1) Liquidity In accordance with JIS K7210-1:2014, MFR (melt flow rate) was measured under conditions of a temperature of 230° C. and a load of 21.2 N (2.16 kg). The measured value was used as an evaluation value of fluidity.
[0105] The pelletized thermoplastic elastomer composition was then injection molded into a plate measuring 120 mm x 120 mm x 2 mm (length x width x thickness) using an injection molding machine with a clamping force of 100 tons (manufactured by Japan Steel Works, Ltd., product name "J100ADS") to obtain a test specimen. The hardness, tensile strength, maximum elongation, compression set, and tribological properties of the obtained test specimen were evaluated.
[0106] (2) Hardness (Duro A) Measurements were performed in accordance with JIS K6253-3:2012 (Duro-A).
[0107] (3) Tensile test Tensile strength (T B ), maximum elongation (E B ) was measured.
[0108] (4) Compression set As an index of elastic recovery, the compression set was measured when compressed by 25% for 22 hours at 70°C in accordance with JIS K6262: 2013. The smaller the compression set value, the better the elastic recovery.
[0109] (5) Sliding properties The coefficient of dynamic friction was measured as an index of the sliding property, and the sliding property was evaluated based on the coefficient of dynamic friction. More specifically, a reciprocating sliding tester (manufactured by Shinto Scientific Co., Ltd., product name "TYPE:38") was used at room temperature under a load of 200 g / 1.5 mm 2 (Surface pressure 133g / mm 2 ) The dynamic friction coefficient of the sheet-like molded product against a spherical glass test piece with a diameter of 10 mm was measured under the conditions of a glass test piece sliding speed of 100 mm / min (1 stroke 50 mm).
[0110] (6) Glass adhesion (6-1) Preparation of glass-bonded body First, a glass plate (100 mm x 100 mm x 2 mm (length x width x thickness)) whose surface had been washed with ethanol was inserted in advance into the split mold of an injection molding machine (manufactured by Hishiya Seiko Co., Ltd., product name "VNT-70S"). Any of the thermoplastic elastomer compositions produced above was injection molded into the cutout (inside the split mold into which the glass plate had been inserted) so as to fit into the cutout (injection temperature 230°C, mold cooling temperature 45°C), and a flat plate (150 mm x 150 mm x 4 mm (length x width x thickness)) was obtained in which the thermoplastic elastomer composition and the glass plate were injection fused. Next, this flat plate was slit into a width of 10 mm to obtain a test piece.
[0111] (6-2) Evaluation of adhesion to glass Using a tensile testing machine (manufactured by Shimadzu Corporation, product name "AG-X"), one end of the above test piece was held and peeled at a peel angle of 180° and a load speed of 200 mm / min, and the peel strength value (unit: N / mm) was used as an index of glass adhesion.
[0112] (7) Adhesion to vulcanized rubber (7-1) Preparation of vulcanized rubber substrate A mixture was obtained by mixing 100 parts by mass of ethylene-propylene-5-ethylidene-2-norbornene terpolymer (product name "EP 57C", manufactured by ENEOS Materials Corporation, ethylene unit content 67% by mass, 5-ethylidene-2-norbornene unit content 4.5% by mass, Mooney viscosity 58), 113 parts by mass of carbon black (product name "Seat SO", manufactured by Tokai Carbon Co., Ltd.), 67 parts by mass of calcium carbonate (product name "Super SSS", manufactured by Maruo Calcium Co., Ltd.), 67 parts by mass of paraffin-based process oil (product name "PW90", manufactured by Idemitsu Kosan Co., Ltd.), 5 parts by mass of activated zinc oxide (manufactured by Sakai Chemical Industry Co., Ltd.), and 1 part by mass of stearic acid (manufactured by ADEKA Corporation) using a Banbury mixer at 50°C, 70 rpm, and for 2.5 minutes. To the total amount (353 parts by mass) of the obtained mixture, 10 parts by mass of a dehydrating agent (product name "Besta PP", manufactured by Inoue Lime Industry Co., Ltd.), 2 parts by mass of a plasticizer (product name "PEG # 4000", manufactured by NOF Corporation), 1 part by mass of a vulcanization accelerator "Noccela MP", 1 part by mass of a product name "Noccela CZ-G", 1.2 parts by mass of a product name "Noccela TET-G", and 2 parts by mass of a product name "Noccela BZ-P" (all manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), and 2 parts by mass of sulfur were added, and the mixture was kneaded at 50 ° C. using an open roll, and then vulcanized at 170 ° C. for 20 minutes to produce a sheet molded to a size of 120 mm × 120 mm × 2 mm (length × width × thickness). This sheet was punched out to a length of 60 mm and a width of 50 mm with a dumbbell cutter, and this was used as an olefin-based vulcanized rubber adherend.
[0113] (7-2) Preparation of bonded body with vulcanized rubber adherend First, the olefin-based vulcanized rubber adherend prepared above was inserted in advance into the split mold of an injection molding machine (manufactured by Japan Steel Works, Ltd., product name "J100ADS"). Either of the elastomer compositions was injection molded (injection temperature 230°C, mold cooling temperature 45°C) into the cutout (inside the split mold with the olefin-based vulcanized rubber adherend inserted) so as to fit into the cutout, and a flat plate (120mm x 120mm x 2mm (length x width x thickness)) was obtained in which the thermoplastic elastomer composition and the thermoplastic elastomer adherend were injection fused. Next, this flat plate was punched out with a JIS-2 dumbbell cutter to obtain a test piece (dumbbell-shaped test piece).
[0114] (7-3) Evaluation of adhesion to vulcanized rubber substrates The test piece was pulled at a load rate of 200 mm / min using a tensile tester (manufactured by Shimadzu Corporation, product name "AG-X"), and the breaking strength value (unit: MPa) was used as an index of vulcanized rubber adhesion.
[0115] (8) Thermoplastic elastomer adhesion (8-1) Preparation of thermoplastic elastomer adherend Celanese's Santoprene 121-73W175 was molded into a sheet measuring 120 mm x 120 mm x 2 mm using an injection molding machine (Japan Steel Works, product name J100ADS). This sheet was punched out with a dumbbell cutter into a length of 60 mm and a width of 50 mm, which was used as a thermoplastic elastomer adherend.
[0116] (8-2) Preparation of bonded structure with thermoplastic elastomer adherend First, the thermoplastic elastomer adherend prepared above was inserted in advance into the split mold of an injection molding machine (manufactured by Japan Steel Works, Ltd., product name "J100ADS"). Next, any one of the thermoplastic elastomer compositions prepared above was injection molded into the cutout (inside the split mold into which the thermoplastic elastomer adherend was inserted) so as to fit into the cutout (injection temperature 230°C, mold cooling temperature 45°C), and a flat plate (120mm x 120mm x 2mm (length x width x thickness)) in which the thermoplastic elastomer composition and the thermoplastic elastomer adherend were injection fused was obtained. Next, this flat plate was punched out with a JIS-2 dumbbell cutter to obtain a test piece (dumbbell-shaped test piece).
[0117] (8-3) Evaluation of adhesion to thermoplastic elastomer substrates Using a tensile tester (manufactured by Shimadzu Corporation, product name "AG-X"), the above test pieces were pulled at a load rate of 200 mm / min, and the breaking strength value (unit: MPa) was used as an index of thermoplastic elastomer adhesiveness.
[0118] 2.3.Evaluation Results The compositions of the thermoplastic elastomer compositions (T-1) to (T-5) used in each Example and Comparative Example are shown in Table 1. The evaluation results of the thermoplastic elastomer compositions prepared in each Example and Comparative Example are shown in Table 2.
[0119] [Table 1]
[0120] [Table 2]
[0121] The components used in Tables 1 and 2 above are as follows: Ethylene-α-olefin copolymer rubber: Product name "EP 501EC", manufactured by ENEOS Materials Corporation, ethylene-propylene-5-ethylidene-2-norbornene terpolymer (ethylene unit content 65.5% by mass, 5-ethylidene-2-norbornene unit content 5.5% by mass) Hydrogenated block copolymer: Product name "TAIPOL-6151", manufactured by Taiwan Synthetic Rubber Co., Ltd. (TSRC), styrene-butadiene-styrene hydrogenated block copolymer, styrene content: 32% by mass, weight average molecular weight: 260,000 Polyolefin resin: Product name "Novatec PP FX4EA", Japan Polypropylene Corporation, propylene random copolymer, density 0.90g / cm 3 , Melt flow rate (230℃, load 21.2N) 5.3g / 10min Crosslinking agent: Trade name "Perhexa 25B-40", NOF Corporation, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane Crosslinking agent: Trade name "Valnoc PM", manufactured by Ouchi Shinko Chemical Industry Co., Ltd., N,N'-m-phenylene bismaleimide Polydimethylsiloxane: Trade name "DOWSIL SH200 Fluid 100cSt", manufactured by Dow Toray, dynamic viscosity: 100cSt Mineral oil-based softener: Product name "Diana Process Oil PW90", manufactured by Idemitsu Kosan Co., Ltd. Anti-aging agent: Trade name "ADEKA STAB AO-60", manufactured by ADEKA Corporation, pentaerythritol tetrakis [3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] Polyolefin containing acid anhydride groups (S-1): Trade name "UMEX 1010", manufactured by Sanyo Chemical Industries, Ltd., maleic anhydride modified polypropylene Silanol-containing polyolefin (S-2): Product name "Linklon PM700N", manufactured by Mitsubishi Chemical Corporation, silane-modified amorphous poly-α-olefin, main chain is a copolymer of propylene and ethylene
[0122] The evaluation results in Table 2 above show that the thermoplastic elastomer compositions of Examples 1 to 8, which contain the (T) component and the (S) component, obtained good results in the evaluation of glass adhesion. In contrast, the thermoplastic elastomer compositions of Comparative Examples 1 to 5, which contain only the (T) component, did not adhere to glass even when injection fusion-bonded.
[0123] The present invention is not limited to the above-described embodiments, and various modifications are possible. The present invention includes configurations that are substantially the same as those described in the embodiments (for example, configurations with the same functions, methods, and results, or configurations with the same purpose and effect). The present invention also includes configurations in which non-essential parts of the configurations described in the above-described embodiments are replaced with other configurations. Furthermore, the present invention also includes configurations that have the same effects as the configurations described in the above-described embodiments, or that can achieve the same purpose. Furthermore, the present invention also includes configurations in which publicly known technology is added to the configurations described in the above-described embodiments.
Claims
1. A window module having a window portion and a window frame portion covering an outer periphery of the window portion, A window module, wherein the window frame portion is made of a composition containing the following component (T) and the following component (S): Component (T): A melt-kneaded product of a composition containing (A) at least one elastomer component selected from the group consisting of an olefin-based thermoplastic elastomer and a styrene-based thermoplastic elastomer, and (B) a thermoplastic resin (excluding those corresponding to component (S)). Component (S): a polymer having at least one functional group selected from the group consisting of a carboxy group, an acid anhydride group, an amino group, and a silanol group
2. The window module according to claim 1 , wherein the (T) component is a melt-kneaded composition comprising the (A) component, the (B) component, and a (C) crosslinking agent.
3. The window module according to claim 1 , wherein the polymer constituting the (S) component is a propylene-based polymer.
4. The window module according to claim 1 , wherein the polymer constituting the component (S) is a styrene-based thermoplastic elastomer.
5. The window module according to claim 1 , wherein the (A) component contains (A1) an olefin-based thermoplastic elastomer.
6. The window module according to claim 5 , wherein the (A1) olefin-based thermoplastic elastomer is an ethylene-propylene-non-conjugated diene copolymer.
7. The component (A) is The window module according to claim 1, comprising (A2) a block polymer having at least two polymer blocks selected from the group consisting of a polymer block A mainly composed of a vinyl aromatic monomer unit, a polymer block B mainly composed of a conjugated diene monomer unit, and a random polymer block C of a vinyl aromatic monomer unit and a conjugated diene monomer unit, or a hydrogenated product thereof.
8. The window module according to claim 1 , wherein the component (B) is an olefin-based resin.
9. 2. The window module according to claim 1, wherein the window portion has a wavelength in the range of 400 nm to 700 nm at which the transmittance is 10% or more.
10. The window module according to claim 1 , wherein the window portion is made of glass, polycarbonate resin, or poly(meth)acrylate resin.
11. A vehicle comprising a window module according to any one of the preceding claims.
12. A first step of melt-kneading (A) at least one elastomer component selected from the group consisting of an olefin-based thermoplastic elastomer and a styrene-based thermoplastic elastomer, and (B) a thermoplastic resin (excluding those corresponding to component (S)); a second step of melt-kneading the melt-kneaded product obtained in the first step with a polymer having at least one functional group (S) selected from the group consisting of a carboxy group, an acid anhydride group, an amino group, and a silanol group; A method for producing a thermoplastic elastomer composition comprising the steps of:
Citation Information
Patent Citations
Primer composition and weather strip
JP2003013006A